Construction of standard pier / Nur Ainin Sofiya Mohamed Sufian - Mohamed Sufian, Nur Ainin Sofiya (Universiti Teknologi MARA, Perak, 2018)
Industrial training is an important phase of a student life. A well planned, properly executed and evaluated industrial training helps a lot in developing a professional attitude. It develops an awareness of the industrial approach to problem solving, based on a broad understanding of process and mode of operation of organization. The aim and motivation of this industrial training is to receive discipline, skills, teamwork and technical knowledge through a proper training environment, which will help me, as a student in the field of information Technology, to develop a responsiveness of the self-disciplinary nature of problems in information and communication technology.